The legislative system of the European Union - García Lupiola, Asier (Journal of the Basque Parliament, 2021)
The current legal system in the European Union was defined by the Lisbon Treaty. Although there were developments in the institutional structure, the pre-existing organization was maintained regarding the distribution of legislative functions, although the relevance of the role played by the European Parliament was increased. This is mainly due to the generalization of the codecision procedure, now officially called the ordinary legislative procedure, which enables the institution elected by universal and direct suffrage by European citizens to exercise the mission that corresponds to it, that is, the exercise of the legislative power, although shared with the Council. At the same time, the functions of the European Parliament were increased in the other normative tools, such as the special legislative procedures and the budgetary procedure. This text analyses all those particularities that make up the legislative system of the European Union today.
Keywords: European Union; legislative system; legislative power; legislative procedure; European Parliament